The psychological cycle behind dental appointment attendance: a cross‐sectional study of experiences, anticipations, and behavioral intentions. Issue 4 (19th February 2016) - Schneider, Annegret; Andrade, Jackie; Tanja‐Dijkstra, Karin; White, Mathew; Moles, David R.
Abstract: Objectives: This study explored a promising theoretical model to explain dental patients' experiences and planning behavior for future appointments. The model predicts that patients pass through a 'psychological cycle' when undergoing a course of dental care: past appointment experiences influence their anticipations for future dental visits, which in turn affect behavioral intentions to attend appointments. Methods: Variables representing the hypothesized model stages and other potentially relevant context variables (dental anxiety, subjective oral health ratings, general anxiety, stress) were assessed by means of a cross‐sectional online survey ( n = 311). Multiple regression analyses were calculated to estimate the model's fit while controlling for potentially confounding factors. Results: Consistent with the hypothesized cycle, recollections of past appointment experiences influenced behavioral intentions to attend future appointments. This association was mediated by evaluations of prior visits and expectations for future appointments. The variables included within this model explained 42% of the variance in attendance intentions when controlling for the potential moderating effects of context variables. Conclusions: The findings highlight the contribution of cognitive factors, such as evaluations and expectations, to patients' attendance intentions. This knowledge could help find ways to improve treatment expectations to foster better dental service utilization.